Relations and gender inequalities as a selection mechanism in migration processes. - Lamela Viera, Carmen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article shows some of the key theoretical problems that the study of feminine migrations has faced through a representative bibliographic selection. The article starts with a classic approach to the migratory phenomenon stressing the natural and positive turn towards an analysis of gender. However it finally suggests that the sociology of gender has much to gain from a deep analysis of the migratory phenomenon in order to get answers which allow a greater generalization that apply to the wide variety of historic and cultural situations.